Development of an IoT-Based Mobile Plastic Shredder for Optimized Waste Management in Batam - Lawi, Ansarullah; Dermawan, Aulia Agung; Kurniawan , Dwi Ely; Yuni Roza; Ardilla, Thania; ., Jaswin (Journal of Applied Informatics and Computing, 2025)
Plastic waste management has become a critical environmental issue, with its improper handling leading to severe ecological and health impacts. This research addresses the challenge by designing and developing an IoT-based mobile plastic shredding machine aimed at improving waste management efficiency, particularly in Batam City, Indonesia. Utilizing Borg and Gall’s R&D framework, this study integrates IoT technology to enhance the machine’s functionality, enabling real-time data collection and remote monitoring through mobile applications. The machine comprises three functional levels: a storage area for raw plastic bottles, a shredding unit with proximity sensors, and a post-shredding storage compartment. Key innovations include weight sensors for automatic material handling and real-time data transmission via the Blynk IoT platform, controlled by an Arduino microcontroller. The modular design ensures portability, easy maintenance, and adaptability for use in various locations, including coastal areas. Prototyping involved integrating proximity sensors, load cells, relays, and motor control systems to ensure smooth operation. The machine demonstrated consistent performance during testing, with its IoT features enabling remote control and monitoring via smartphones. This facilitates optimized waste collection and contributes to reducing environmental pollution caused by plastic waste. The IoT-based mobile plastic shredding machine not only enhances waste management efficiency but also supports sustainability goals. Its portability and environmentally friendly design make it a practical solution for managing plastic waste in underserved areas. This innovation provides a significant step toward addressing the global plastic waste crisis, aligning with technological advancements to promote sustainable waste management practices.